An interactive way of reading and playing video games through ‘Read and Play’ / Izzatul Hasanah Mohd Rosli and Afifah Fadhlullah - Mohd Rosli, Izzatul Hasanah; Fadhlullah, Afifah (Universiti Teknologi MARA, Kedah, 2023)
Video games, in general, are electronic games that can be interacted with using input devices such as computers and gaming consoles. There are some people who perceive video games as having no educational value, as it is often presented negatively by the media. Thus, the fact that video games can be educational is always overlooked due to the public's negative perception, especially the older generation. “Read and Play” is a combination of an e-book and short video games targeted towards adolescents. A survey consisting of 21 respondents from different age groups between 11 to 24 years old was carried out to obtain their perceptions of reading short stories through video games. The finding reveals that gamification of reading in video games show positive feedback from adolescents and can encourage them to read more effectively. This study aims to help improve reading skills among adolescents through video games, to identify the factors that influence adolescents to read effectively through video games and to provide video games that are educational in content. In terms of novelty, this product is different in which it is an adaptation of 5 classic children short stories that are made into mini video games that caters to the targeted age group. The benefits of this product are immense as video games can provide “edutainment”, which is both educational and entertaining, it can make reading fun and interactive by using gamification and to heighten interest in reading through reading and play. This product has the potential to be commercialized to adolescents being the target users and priced at RM5 since it is a small-scale video game with simple gaming mechanics. A digital gaming marketplace called “itch.io” is where this product is advertised and sold by most less experienced developers who publish their video games to reach local and global consumers.